Exploring the evolution of hollow fiber membrane applications in wastewater treatment - Fulufhelo H. Mudau; Zebron Phiri; Machawe M. Motsa; Lueta-Ann de Kock (Desalination and Water Treatment)
The use of membrane processes in wastewater treatment has grown rapidly due to advancements in materials, fabrication, and modification techniques. This study presents a comprehensive bibliometric analysis of research on hollow fiber membranes (HFMs) for wastewater treatment, encompassing 620 publications indexed in the Web of Science database between 2014 and 2023. Using the PRISMA framework, Bibliometrix, and VOSviewer, we mapped global research output, identified leading contributors, and analyzed thematic trends. The findings reveal a steady growth in HFM-related research, with China emerging as the leading contributor, reflecting policy-driven advancements in water treatment and reuse technologies. Keyword co-occurrence and trending topics analyses highlight persistent priorities such as membrane fouling mitigation, optimization of membrane bioreactors, and the increasing integration of HFMs into resource recovery applications. Significant progress has been made in leveraging HFMs for nutrient and organic matter recovery, thereby transforming wastewater into a valuable resource. Case studies demonstrate the use of HFMs for phosphorus, nitrogen, and potassium extraction, as well as for recovering volatile fatty acids, proteins, and hydrocarbons from diverse effluents. In addition to nitrogen recovery, notable emerging trends encompass desalination, forward osmosis, and oily wastewater treatment. These developments underscore the dual role of HFMs as high-performance separation technologies and key enablers of circular economy strategies in wastewater management. Despite these advances, challenges such as membrane fouling, high operational costs, and limited scalability persist. Furthermore, integrating HFMs with pretreatment technologies and developing novel materials are pivotal for minimizing fouling and enhancing operational performance across various wastewater types. This study provides an overview of HFM-based wastewater treatment, identifies knowledge gaps, and outlines future research directions that aim to advance sustainable and resource-efficient wastewater treatment solutions.